If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2m + 3 = 3m + 4 Reorder the terms: 3 + 2m = 3m + 4 Reorder the terms: 3 + 2m = 4 + 3m Solving 3 + 2m = 4 + 3m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-3m' to each side of the equation. 3 + 2m + -3m = 4 + 3m + -3m Combine like terms: 2m + -3m = -1m 3 + -1m = 4 + 3m + -3m Combine like terms: 3m + -3m = 0 3 + -1m = 4 + 0 3 + -1m = 4 Add '-3' to each side of the equation. 3 + -3 + -1m = 4 + -3 Combine like terms: 3 + -3 = 0 0 + -1m = 4 + -3 -1m = 4 + -3 Combine like terms: 4 + -3 = 1 -1m = 1 Divide each side by '-1'. m = -1 Simplifying m = -1
| 10x-73=107 | | x-4=x(.5) | | 90=135/t | | 7-v=-70 | | 10(6)=12(x-4) | | -7(1-4m)=13(2m-2) | | 12*8=10*x | | -17y-231=347 | | 2(x-3)-3x=4x-1 | | X^2-120=7X | | 14b+145=19 | | 6x-10=2x+42 | | 40w+3(2w)=552 | | (x+20)+(25x-2)=70 | | s^2-17s-60= | | 21-(-3n)=6 | | 3cos-4sin=0 | | 32-x=-14 | | 8s+5c=67 | | 810=61m+b | | 2x+2(x+6)=32 | | (4x-9)+(6x-22)=59 | | (x-4)^2/3=100 | | 3x^3+22x^2-45=0 | | 3-24x/10-1-2x/2=-1/10(3x-4) | | 5x-2y-12=0 | | 7y=6x-41 | | 3w+3= | | (2x)+(x+40.5)=123 | | 1.5+1.2=5.7 | | x/-34=6 | | 9x^2+9x-6=0 |